2014
DOI: 10.1021/jz500494s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electrochemical Differences in Nonaqueous Li–O2 and Na–O2 Batteries

Abstract: We present a comparative study of nonaqueous Li-O2 and Na-O2 batteries employing an ether-based electrolyte. The most intriguing difference between the two batteries is their respective galvanostatic charging overpotentials: a Na-O2 battery exhibits a low overpotential throughout most of its charge, whereas a Li-O2 battery has a low initial overpotential that continuously increases to very high voltages by the end of charge. However, we find that the inherent kinetic Li and Na-O2 overpotentials, as measured on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
301
1
12

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(337 citation statements)
references
References 37 publications
23
301
1
12
Order By: Relevance
“…X‐ray diffraction confirms that the cube‐shaped discharge product is NaO 2 (Figure S3, S4) in accord with many previous reports on similar cells 1b,1c, 2a,2b, 3a. After discharge or recharge to 2.8 and 3.65 V, 4.1, 4.3, and 7.2 %, respectively, of the DMA at the sample points ②, ③, and ④ was converted into DMA‐O 2 (Figure 1 b).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…X‐ray diffraction confirms that the cube‐shaped discharge product is NaO 2 (Figure S3, S4) in accord with many previous reports on similar cells 1b,1c, 2a,2b, 3a. After discharge or recharge to 2.8 and 3.65 V, 4.1, 4.3, and 7.2 %, respectively, of the DMA at the sample points ②, ③, and ④ was converted into DMA‐O 2 (Figure 1 b).…”
supporting
confidence: 91%
“…Previously it was reported that most parasitic chemistry occurs during discharge and less on charge 2a, 3a. Charging above around 3.5 V caused the number of O 2 per e − evolved to deviate more significantly from one than at lower voltages.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The suggested mechanism defined the role of water as an active part of surface intermediates, through hydrogen bonding to LiO 2 , which promotes the formation of Li 2 O 2 and the resulting partial dissociation of H 2 O to HO 2 and OH − 13. Superior discharge capacity has been demonstrated with benzoic and acetic acid in Na‐O 2 , along with phenol and ethanol in Li‐O 2 , providing additional evidence for this phenomenon 6a,6b…”
mentioning
confidence: 85%
“…The voltage gap between discharge and charge is 100 mV for Na-O2 and 50 mV for K-O2, compared to 1 V for Li-O2. [8][9][10] This variation is attributed to the different type of discharge product, superoxide in Na-O2/K-O2 versus peroxide in Li-O2. Recently the chemistry at the cathode in the aprotic Li-O2 battery has been established and two competitive routes have been demonstrated on discharge, the solution route and the surface route.…”
Section: Cathodementioning
confidence: 99%